(untitled) (Eurasian Journal of Philology Science and Education, 2025)
In today’s global education system, the importance of developing digital literacy and competence among higher education students is steadily increasing. This article examines modern approaches and methods to enhance the digital competence of students majoring in “Kazakh language and literature.” The objective of the study is to systematize and analyze contemporary approaches and methods aimed at improving the digital competence of these students, as well as to assess the actual state of students’ digital and qualitative indicators based on a conducted survey. In a rapidly developing society driven by digital technologies, the ability to effectively use information and communication technologies (ICT) is a fundamental principle that defines the digital competence of future specialists in the humanities. Identifying effective pedagogical practices and technologies that contribute to the development of digital skills in university students supports the formation of learners as modern professionals. During the practical research, a survey was developed for students majoring in “Kazakh language and literature,” where respondents assessed their skills in digital technologies, the frequency of ICT use in the learning process, and the share of digital methods in education. The collected data revealed significant differences in students’ mastery of basic and advanced digital tools. Additionally, the survey results showed strong interest in project-based learning and interactive teaching formats. A literature review analyzed the concepts of digital competence and digital literacy, exploring modern educational technologies (EdTech) and the “Edutainment” concept (combining education and entertainment) as methods to increase motivation and teaching effectiveness. Interactive educational platforms, distance learning, and game-based formats were shown to facilitate the development of students’ digital skills and foster their creative potential. The discussion section highlights the necessity of systematically integrating modern digital methods into the educational process, training educators, and enhancing the technical infrastructure of higher education institutions. This will ensure that students successfully adapt to the digital environment in accordance with contemporary requirements. Keywords: digital technology, space, competence, EdTech, digital competence, digital learning, student, modern methods, knowledge, skills.